Applying integrated assessment methodologies to air quality plans: Two European cases. Issue 65 (November 2016) - Miranda, A.I.; Relvas, H.; Viaene, P.; Janssen, S.; Brasseur, O.; Carnevale, C.; Declerck, P.; Maffeis, G.; Turrini, E.; Volta, M.
Highlights: Integrated Assessment Modelling was used for selecting cost-efficient emission abatement measures. Scenario and optimization approaches were applied to Brussels and Porto urban areas, respectively. The selection of abatement measures to be included in the modelling is one of the most challenging tasks. Abstract: Air pollution Integrated Assessment Models (IAM) can be used for determining how emissions should be reduced to improve air quality and to protect human health in a cost-efficient way. The application of IAM is also useful to spread information to the general public and to explain the effectiveness of proposed Air Quality Plans. In this paper, the application of the RIAT+ system to determine suitable abatement measures to improve the air quality at a regional/local level is presented for two European cases: the Brussels Capital Region (Belgium) and the Porto Urban Area (Portugal). Both regions are affected with PM10 or NO2 concentrations that exceed the limit values specified by the European Union legislation. To properly assess air quality abatement measures a surrogate model was used, allowing the implementation of an efficient optimization procedure. This model is derived in both cases through a set of simulations performed using a Chemistry Transport Model fed with different emission reduction scenarios. In addition, internal costs (due to the implementation of emission reduction measures) and external costs (due to population exposure to air pollutant concentrations) of policy options were considered. The application of this integrated assessment modelling system in scenario (Brussels case) and optimization (Porto) modes contributes to identifying some advantages and limitations of these two approaches and also provides some guidance when urban air quality has to be assessed.